Incidentes laborales en trabajadores de catorce ciudades del Perú: causas y posibles consecuencias - Mejia, Christian R (2019)
Objective: determine the perception of the causes and possible consequences of events dangerous to the health of Peruvian workers. Material and Methods: multicenter analytical cross-sectional study, in fourteen Peruvian cities, inquired about the perception of the causes and possible consequences that had caused the dangerous health events. We searched for associations between the variables. Results: 1772 workers had a work incident, due to the distraction of the worker (66%) and the one that was not signaling the danger (44%); the most serious repercussions would have occurred in the worker (74%) and his family (66%), but it meant a great economic loss for the company. Conclusions: it was found that the perceptions of the consequences of a work incident could affect workers, family and company, these results should be considered to improve working conditions and the information that employees receive.